ECERIFERUM 10 Encoding an Enoyl-CoA Reductase Plays a Crucial Role in Osmotolerance and Cuticular Wax Loading in Arabidopsis - Fukuda, Norika; Oshima, Yoshimi; Ariga, Hirotaka; Kajino, Takuma; Koyama, Takashi; Yaguchi, Yukio; Tanaka, Keisuke; Yotsui, Izumi; Sakata, Yoichi; Taji, Teruaki (Frontiers in Plant Science, 2022)
Acquired osmotolerance induced after salt stress is widespread across Arabidopsis thaliana (Arabidopsis) accessions (e.g., Bu-5). However, it remains unclear how this osmotolerance is established. Here, we isolated a mutant showing an acquired osmotolerance–defective phenotype (aod2) from an ion-beam–mutagenized M2 population of Bu-5. aod2 was impaired not only in acquired osmotolerance, but also in osmo-shock, salt-shock, and long-term heat tolerances compared with Bu-5, and it displayed abnormal morphology, including small, wrinkled leaves and zigzag-shaped stems. Genetic analyses of aod2 revealed that a 439-kbp region of chromosome 4 was translocated to chromosome 3 at the causal locus for the osmosensitive phenotype. The causal gene of the aod2 phenotype was identical to ECERIFERUM 10 (CER10), which encodes an enoyl-coenzyme A reductase that is involved in the elongation reactions of very-long-chain fatty acids (VLCFAs) for subsequent derivatization into cuticular waxes, storage lipids, and sphingolipids. The major components of the cuticular wax were accumulated in response to osmotic stress in both Bu-5 WT and aod2. However, less fatty acids, primary alcohols, and aldehydes with chain length ≥C30 were accumulated in aod2. In addition, aod2 exhibited a dramatic reduction in the number of epicuticular wax crystals on its stems. Endoplasmic reticulum stress mediated by bZIP60 was increased in aod2 under osmotic stress. The only cer10 showed the most pronounced loss of epidermal cuticular wax and most osmosensitive phenotype among four Col-0–background cuticular wax–related mutants. Together, the present findings suggest that CER10/AOD2 plays a crucial role in Arabidopsis osmotolerance through VLCFA metabolism involved in cuticular wax formation and endocytic membrane trafficking.